Overcrowding, Drugs Abuse and Violence vs. Rehabilitation Interviews and Perceptions of a Sample of Prisoners - Ravagnani, Luisa; Ricci Bitti, Nicolò (International Journal of Criminology and Sociology, 2024)
Based on the interviews collected and conducted during the data gathering process for the documentary "11 days: within the prison walls”, some inmates from the prison of Nerio Fischione based in Brescia (Italy) decide to share their stories to a microphone and storytellers. The voices provide a sincere look, suitable for investigating the subjective perceptions that inmates have regarding the prison environment, exploring the complexities of their experiences. What emerges from the stories is a place that is far away from the rehabilitation purpose that it should have. The enormous issue of overcrowding, drug pills treatment abuse, and, above all, the pervasive violence within the corridors of the facility. The punitive function seems to prevail and is doubly enacted: firstly, through the nature of the prison itself, and secondly, through the prison conditions that prevent from any possibility to start a positive path. This article aims to contribute to the existing academic debate providing an insight from the prisoners’ perception about their personal experience, focusing on the issues that most frequently emerge from their testimonies: the lack of significance that they experience on a daily basis.